Noninvasive treatment of keloid using customized Re‐188 skin patch. Issue 5 (16th June 2017) - Bhusari, Priya; Shukla, Jaya; Kumar, Munish; Vatsa, Rakhee; Chhabra, Anupriya; Palarwar, Kanchan; Rathore, Yogesh; De, Dipanker; Kumaran, Sendhil; Handa, Sanjeev; Mittal, B. R.
Abstract: Keloids are developed as fibrotic scar at the site of surgery or trauma and often enlarge beyond the original scar margins. Re‐188 colloid coated customized patch was superficially fixed onto the lesion for 3 hrs. The same patch was reapplied on the lesion on third day for 3 hrs. The patients were followed up at 1, 3, 6 and 12 months post treatment. The size and elevation of the keloid lesion was reduced after treatment. The total radiation dose from the patch (day‐1 and day‐3) was 100 Gy/mCi of Re‐188. The radioactive patch treatment of keloids is noninvasive, painless and safe with prolonged outcome.